Growth differentiation factor 15 as a useful biomarker of heart failure in young patients with unrepaired congenital heart disease of left to right shunt. Issue 6 (June 2020) - Kagiyama, Yoshiyuki; Yatsuga, Shuichi; Kinoshita, Masahiro; Koteda, Yusuke; Kishimoto, Shintaro; Koga, Yasutoshi; Suda, Kenji
Highlights: Growth differentiation factor (GDF) 15 positively correlated with modified Ross score and oxygen extraction ratio. GDF 15 also negatively correlated with estimated glomerular filtration rate. GDF 15 did not correlate with the pulmonary to systemic blood flow ratio. High modified Ross scores were strongly predicted by elevation of GDF 15. Abstract: Background: Growth differentiation factor 15 (GDF 15) is a member of the transforming growth factor-beta superfamily and is considered to be a useful biomarker for severity of heart failure (HF) in repaired congenital heart disease (CHD). The aim of this study was to determine the clinical implication of GDF 15 in children with unrepaired CHD. Methods: Subjects included 69 patients (≤14 years old) who had unrepaired CHD with left to right shunt and underwent cardiac catheterization. Demographic and hemodynamic data, including oxygen demand–supply relationship, were collected from medical records. Severity of HF was evaluated using modified Ross score. Serum GDF 15 levels were determined using enzyme-linked immunosorbent assay and correlated with patients' demographics, hemodynamic data, and blood chemistry data. Results: Subjects had median age of 71 (range 1–173) months and simple acyanotic CHDs with mean pulmonary to systemic flow ratio of 2.0 (1.0–5.6), median N-terminal pro type Brain natriuretic peptide (NT-pro-BNP) of 162.8 (17.1–8789) pg/mL, and median GDF 15 of 242.1 (13.6–1116.7) pg/mL. GDF 15 significantly positively correlated with the modified Ross score, mean pulmonary artery pressure, oxygen extraction rate (OER), and Ln NT-pro-BNP, but negatively correlated with age, oxygen delivery and its components, and estimated glomerular filtration rate (eGFR). Multiple linear regression analysis revealed significant correlation of GDF 15 levels with the modified Ross score, OER, and eGFR. Conclusions: GDF 15 mainly reflects oxygen demand–supply relationship and can be used as a diagnostic marker of HF in unrepaired CHD with left to right shunt for a wide range of age and diagnoses.